Determining the index of injuries requiring specialist treatment during boulder climbing on an artificial climbing wall - Zieliński, Grzegorz; Zięba, Estera; Ginszt, Michał (Journal of Education, Health and Sport, 2019)
Introduction: Climbing was accepted as the official discipline at the Olympic Games in Tokyo in 2020. It is a sport that is becoming one of the most popular from extreme sports. The aim of the study is to assess the climbers’ reported injuries during bouldering climbing, requiring specialized treatment (calls to the emergency medical team, hospitalization, surgical sewing). Material and methods: Materials for analysis were made available by the Climbing Center. Climbers were registered in the period from November 2018. until August 2019. All climbers expressed a conscious desire to participate in climbing classes, knew the risks associated with practicing the sport and took full responsibility for their activities, which was confirmed in writing. The trained staff was present during all climbing classes. Results: Data were collected for 272 days, during which the climbing wall was open 1805 hours. At that time, 4,315 people with diverse experience climbed it. Three injuries requiring intervention of the emergency medical team and hospitalization were registered. This represents 1.66 injuries per 1000 hours of climbing and 0.7 injuries per 1000 people. Conclusions: • Bouldering climbing on an artificial wall is characterized by an injury index requiring specialized treatment in the value of 1.66 injury per 1000 hours of climbing. • Further studies should also focus on comparing different extreme disciplines in terms of injury rates. • Further studies on the frequency of injuries in climbing should be characterized by a normalized system of assessment of injuries and time of event registration depending on the type of discipline (difficulty climbing, bouldering), location (hall, rock climbing) and season.